Definition of trAnscatheter heart Valve orIeNtation in biCuspId aortic valve: The DA VINCI pilot study - Tarantini, Giuseppe; Fabris, Tommaso; Nai Fovino, Luca; Cardaioli, Francesco; Pergola, Valeria; Montonati, Carolina; Rodinò, Giulio; Cabrelle, Giulio; Massussi, Mauro; Scotti, Andrea; Zuccarelli, Vittorio; Sciarretta, Tommaso; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Specific techniques to align the neo-commissures have been reported for supra-annular transcatheter heart valve (THVs) during transcatheter aortic valve replacement (TAVR) in tricuspid aortic valve. However, less is known about the rate of successful commissural alignment with current implantation techniques in patients with bicuspid aortic valve (BAV). Methods: The DA VINCI study is a prospective registry enrolling consecutive patients with BAV stenosis undergoing TAVR with last generation supra-annular THVs implanted with a cusp overlap view-based commissural alignment. Patients underwent pre- and post-TAVR computed tomography (CT) and coronary angiography. The study endpoint was the rate of favorable THV/coronary overlap, defined as an angle >40° between the neo-commissures and coronary ostia. Other endpoints were the rates of successful THV alignment with respect to the raphe and of selective CA after TAVR. Different virtual THV alignment models were tested to identify which one would produce the lower degree of THV/coronary overlap. Results: Thirty-four patients with BAV with right-left raphe undergoing TAVR (23 with Evolut Pro/Pro+ and 11 with Acurate Neo2) were included. At pre-TAVR CT, moderate/severe cusp asymmetry was found in 50% of patients, severe coronary ostia eccentricity was observed in 47.1% for the RCA vs. 8.8% for the LCA (P<0.007). Correct TVH orientation was achieved in 29 cases. At post-TAVR CT, optimal THV alignment/mild misalignment to the raphe was observed in 86.2%, but a moderate/severe overlap with the coronaries was seen in 13.7% for the RCA and 44.8% for the LCA (P=0.019). After TAVR, selective RCA cannulation was possible in 82.8% vs. 75.9% for the LCA (P=0.74), while combined selective CA of both coronaries was possible in less than two-thirds of the patients. Virtual THV alignment in the coronary ostia overlap view assuming a hypothetical circular THV expansion produced an optimal THV/coronary overlap in almost 90% of cases. Conclusions: In BAV anatomy, conventional commissural alignment techniques are associated with higher rates of THV misalignment and of moderate/severe neo-commissure overlap with the coronary ostia, resulting in lower rates of selective CA after TAVR. A modified THV orientation technique based on the coronary ostia overlap view might be preferable in BAV patients.